(untitled) (International journal of artificial intelligence, 2025)
Ethnolexis represents a significant layer of vocabulary that reflects the cultural, historical, and social life of a nation. This article examines the study of ethnolexical units in the Uzbek language, focusing on their classification, sources, and linguistic as well as cultural value. The research highlights the importance of ethnolexis in preserving national identity and understanding the worldview of the Uzbek people.